EURASIA, GEOPOLITICS, AND AMERICAN FOREIGN POLICY - TCHANTOURIDZE, Lasha (CENTRAL ASIA AND THE CAUCASUS, 2008)
Eurasia, a geopolitical conceptual construct of the 20th century, has been analyzed from diverse perspectives. Many distinguished scholars have contributed to this effort. Such analytical exercises inevitably call for further study and commentary on complex dynamics of Eurasian political and economic processes. This global corner currently attracts substantial international attention from great powers and small players alike. Global geopolitical corners have historically been defined by great powers involved in theatrics of international struggle. International politics cannot avoid clashes of interests among participants; such is the nature of the internation-al system composed of nation-states. Currently, the Russian Federation and the United States of America vying to have their vision of regional order prevail in Eurasia. Fortunately, their competition lacks drama of the Cold War, but is no less important, especially for the Eurasian countries directly affected by potential outcomes. To a considerable extent, Moscow and Washington continue espousing incompatible ways of doing global politics. The Russians still see the world divided among discrete spheres of influence, resembling the divisions of the Cold War. Such perceptions of the divided world are no longer global in scope, and not necessarily as rigid as they used to be, but ultimately Moscow’s conception of great power rests on controlled access to geo-graphic space they could call solely their own. On the other hand, the Americans continue to be com-mitted to the ideas of the open world, free markets, and economic exchange unimpeded by political roadblocks. Washington has been largely married to such a vision since the 1940s, and American foreign policy makers have consistently and deliberately pursued policies that encourage maximum openness and interdependency in the world. Clash between these two visions largely determines the boundaries of Eurasia as a geopolitical construct, and its outcomes will be paramount for the overall direction of its many political processes.